Analisis Finansial Pembibitan Kelapa Sawit pada Produsen Benih Di Provinsi Sumatera Utara - Tarigan, Eva Elfriani; Akoeb, Erwin Nyak; Hasibuan, Syahbudin (Universitas Medan Area, 2021)
This study aims to examine the costs incurred / production costs in the oil palm nursery business in North Sumatra Province, the revenues received in the oil palm nursery business in North Sumatra Province, the profits received in the oil palm nursery business in North Sumatra Province and and to know the level of efficiency of oil palm seed nurseries. The research was conducted at three seed producers in North Sumatra Province, namely PPKS Medan, PT. PP. Lonsum Indonesia, Tbk and PTPN IV. From the research, it was obtained (a) The production costs of oil palm nursery per seed ready for planting at each company / seed producer PT. PP. Lonsum Indonesia, Tbk. in the amount of Rp. 34,016, PPKS Medan amounting to Rp. 33,716 and PTPN. IV amounting to 34,061; (b) The selling price of palm oil is in the range of Rp. 38,000 - Rp. 42,000; (c) Revenue per seed in the oil palm nursery at PT. PP. Lonsum Indonesia, Tbk. in the amount of Rp. 34,016, PPKS Medan amounting to Rp. 31,493 and PTPN IV in the amount of Rp. 29,265; (d) Net income for oil palm nurseries at PPKS Medan is Rp. 11,398, PTPN IV in the amount of Rp. 7,844 and the smallest PT. PP. Lonsum Indonesia, Tbk. in the amount of Rp. 7,235; (e) Efficiency of oil palm nursery business at PTPN IV 1.60, PPKS Medan 1.30 and PT. PP. Lonsum Indonesia, Tbk. 1.27.